Influence of social media on tourism – especially among students of the University of Debrecen - Ráthonyi, Gergely (Applied Studies in Agribusiness and Commerce, 2013)
Derive from the characteristic, decisions connected with travelling have high risk for the travellers therefore they try to collect more detailed information and thoroughly map decision alternatives in order to decrease uncertainty. Wide spread of the Internet and rapid technological evolution have revolutionized all industries in the World especially tourism. Platform of tourism increasingly get to the Internet nowadays which is vitally important because tourism is an informationbased and information-intensive industry. Thanks to development of the internet tourists have an opportunity to access such information and purchasing opportunities which were available with the help of intermediaries earlier. Providing wide range of possibilities, Web 2.0 fundamentally changed the way of tourists’ information search behaviour and travelling decision making. This article collects some of the most significant new applications (social networking sites, blogs) in tourism – examine them from the two sides of tourism (demand, supply) – which principally based on active participation of users. Furthermore an offline questionnaire was made in order to survey the social media usage of the student (University of Debrecen, Centre for Agricultural and Applied Economic Sciences) during their leisure travel planning process. Although findings of the study reveal that vast majority of students use social networking sites every day, they don’t really use these platforms during their trip planning process. Among students, friends and relatives are the most important and the most trustworthy source of information due to characteristics of sample.